2020
DOI: 10.1002/pros.24064
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory infiltration is associated with AR expression and poor prognosis in hormone naïve prostate cancer

Abstract: Background Tumor microenvironment inflammatory infiltration is proposed as a protumorigenic mechanism for prostate cancer with proinflammatory cytokines stimulating androgen receptor (AR) activity. However, association with patient prognosis remains unclear. This study derives an inflammatory gene signature associated with AR expression and investigates CD3+ and CD8+ T‐lymphocyte infiltration association with AR and prognosis. Methods Gene profiling of inflammatory related genes was performed on 71 prostate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In previous studies, we isolated thirteen dibenzocyclooctadiene lignans and neolignans, namely schisantherin B ( McAllister et al, 2020 ), tigloylgomisin P ( Butler and Huang, 2021 ), schirubrisin B ( Lee et al, 2018 ), schisantherin D ( Tai et al, 2011 ), (+)-deoxyschizandrin ( Liu et al, 2012b ), (+)-gomisin K3 ( Karakullukcu et al, 2011 ), angeloylgomisin H ( Sung et al, 2021 ), 3, 7-dihydroxy-1, 2, 13, 14-tetramethoxydibenzocyclooctadiene 12-O-β-D-glucopyranoside ( Vitório et al, 2020 ), schisandrathera B ( Jeong et al, 2022 ), meso-dihydroguaiaretic acid ( Galietta, 2022 ), schisandrathera D ( Seo et al, 2018 ), 4,4-bis(4-hydroxy-3-methoxyphenyl)-2,3-dimethyl-1-butanol ( Seo et al, 2016 ), and schisandrathera C ( Song et al, 2018 ), from the leaves of S. sphenanthera ( Figure 1 ). Their chemical structures, including absolute configurations were determined extensively by HR-ESI-MS, NMR, and ECD spectra and comparing their NMR data with that in reported literature ( Mai et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we isolated thirteen dibenzocyclooctadiene lignans and neolignans, namely schisantherin B ( McAllister et al, 2020 ), tigloylgomisin P ( Butler and Huang, 2021 ), schirubrisin B ( Lee et al, 2018 ), schisantherin D ( Tai et al, 2011 ), (+)-deoxyschizandrin ( Liu et al, 2012b ), (+)-gomisin K3 ( Karakullukcu et al, 2011 ), angeloylgomisin H ( Sung et al, 2021 ), 3, 7-dihydroxy-1, 2, 13, 14-tetramethoxydibenzocyclooctadiene 12-O-β-D-glucopyranoside ( Vitório et al, 2020 ), schisandrathera B ( Jeong et al, 2022 ), meso-dihydroguaiaretic acid ( Galietta, 2022 ), schisandrathera D ( Seo et al, 2018 ), 4,4-bis(4-hydroxy-3-methoxyphenyl)-2,3-dimethyl-1-butanol ( Seo et al, 2016 ), and schisandrathera C ( Song et al, 2018 ), from the leaves of S. sphenanthera ( Figure 1 ). Their chemical structures, including absolute configurations were determined extensively by HR-ESI-MS, NMR, and ECD spectra and comparing their NMR data with that in reported literature ( Mai et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prostate cancer is characterized by the expression of androgen receptors and prostate-specific antigen markers that have a considerable impact on its development. Therefore, hormone therapies for prostate cancer often target these markers ( McAllister et al, 2020 ). However, patients with prostatic small-cell neuroendocrine carcinoma frequently face restrictions in terms of their treatment, including hormone therapy ( Butler and Huang, 2021 ), since androgen receptors and prostate-specific antigen markers are not expressed in this type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an association between the densities of CD8+ T lymphocytes in the peripheral blood and the prognosis of various types of cancers, including non-small cell lung, breast, colorectal, pancreatic and bladder cancers [10][11][12][13][14]. In prostate cancer (PCa), most studies have focused on the associations between intratumoral T lymphocyte subpopulations and clinical outcomes [15][16][17][18]. However, such analyses require prostatic tumor tissue, which is not always acquirable and, in many cases, the collected tissue material is not sufficient for exhaustive analyses.…”
Section: Introductionmentioning
confidence: 99%